Complexo Candida guilliermondii: identificação molecular, prevalência de espécies de interesse clínico e susceptibilidade aos antifúngicos - Pedoni, Diego Betto [UNIFESP] (2018)
Candida guilliermondii today represents a complex of emerging species, some of them of clinical importance, having been described in 1912 by Castellani et al., from sputum culture of a patient with bronchial infection. It is currently responsible for 1-25% of the bloodstream infections caused by Candida sp. in different geographic regions. Despite biological variation of this complex in the world, these isolates of C. guilliermondii are characterized as a single taxonomic unit when identified by phenotypic methods. However, the molecular analysis of genomic DNA allows the differentiation of 7 distinct species in this complex: C. guilliermondii sensu stricto (Meyerozyma guilliermondii), C. fermentati (Meyerozyma carribicca), C. smithsonii, C. athensensis, C. elateridarum, C. carpophila and C. glucosophila. To date, only three species of the complex have been associated with infections in humans: C. guilliermondii, C. fermentati and C. carpophila. There are few data on putative biological and clinical peculiarities of the infections caused by the species of this complex, and their prevalence in medical centers in Brazil and Latin America is unknown. Objectives: To determine the prevalence of different species of the C. guilliermondii complex in episodes of candidemia sequentially documented in sentinel medical centers, standardize strategies for identifying species of the complex and to assess the in vitro susceptibility profile to antifungal of these agents isolates. Material and Methods: A total of 150 isolates obtained from patients attended at 18 medical centers in Brazil and Latin America, initially identified as belonging to C. guilliermondii complex, were submitted to identification by sequencing of the ITS rDNA regions. For the RFLP a PCR of the ITS region of the rDNA was performed, and the amplified DNA fragment was digested with the enzyme Taq I. Refering to the proteomic profile of these isolates, the protein profiles were obtained on the Bruker Daltonics system and assembly of the in-house library. In vitro susceptibility tests were performed according to CLSI document M27-A3 and M27-S4, using antifungal the agents: amphotericin B (AMB), fluconazole (FLC), voriconazole (VOR) and anidulafungina (AND). Results: Among the 150 isolates studied, 135 isolates were identified as C. guilliermondii sensu stricto, 13 isolates as C. fermentati and 2 isolates as C. carpophila. Acording the RFLP assay, it was possible to verify that C. guilliermondii sensu stricto isolates presented a banding profile with 2 bands (~ 250 and 190 bp) and C. fermentati and C. carpophila with 3 bands (~ 250.190 and 150 bp). We created a robust proteomic database with 5 profiles of C. guilliermondii and C. fermentati isolates. In general, in the antifungal susceptibility tests, C. fermentati isolates presented higher geometric means of MICs for FLC, AND and AMB (3.79 μg / mL, 2.11 μg / mL and 1 μg / mL, respectively) ) compared to C. guilliermondii sensu stricto (2.70 μg / mL, 1.77 μg / mL and 0.66 μg / mL, respectively). For the MIC values for VOR, both obtained the same geometric mean of 1 μg / mL. Conclusion: Sequencing of regions of the ribosomal gene allowed accurate identification of all the isolates tested. Using the RFLP technique it was possible to discriminate C. guilliermondii sensu stricto from C. fermentati, but it was not possible to discriminate C. carpohila from C. fermentati. We created a proteomic database capable to discriminate isolates of C. guilliermondii sensu stricto and C. fermentati. In the study, the clinical isolates of C. fermentati presented lower susceptibility to the antifungal agents FLC, AND and AMB, when compared to C. guilliermondii sensu stricto isolates.